Shallow tunneling's impact on surface settlements - Mohamed Djenane; Kamel Bezih (The Journal of Engineering and Exact Sciences)
The research described in this paper deals with the impact of shallow tunneling on surface settlements in urban areas. The study focuses on carrying out a numerical analysis and a parametric geotechnical study to investigate the effects of tunnel excavation on the surface ground, particularly with regard to distortion and potential damage to structures above the tunnel. To carry out the study, the researcher used a finite element method (FEM) software package called Plaxis. This software is commonly used for geotechnical analysis and allows simulating and analyzing the subsurface conditions in Algiers underground in the context of excavating a shallow tunnel. The New Austrian Tunnelling Method (NATM) excavation method was chosen for the study. The results of the numerical analysis are presented in terms of displacements. The results indicate that ground flow has a significant influence on ground movement, probably contributing to surface settlement. However, the effect of tunnel excavation on the lowering of the water table and Young's modulus (a measure of soil stiffness) is relatively small in comparison. The research provides valuable information on the potential impacts of shallow tunneling in urban areas and the factors that play a crucial role in determining the extent of ground movement and surface settlement. By using numerical analysis and conducting a parametric geotechnical study, and gives valuable insights into the potential impacts of shallow tunnelling in urban areas and the factors that play a crucial role in determining the extent of ground movements and surface settlements. By using numerical analysis and conducting a geotechnical parametric study, and contributes to a better understanding of the behavior of the ground during tunnelling operations in Algiers. The findings can be helpful in designing future tunnelling projects to mitigate potential risks to structures and infrastructure located above the tunnels.